2019
DOI: 10.1159/000502154
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Obesity on Work Ability, Respiratory Symptoms, and Lung Function in Adults with Asthma

Abstract: Background: Asthma is defined by variable respiratory symptoms and lung function, and may influence work ability. Similarly, obesity may contribute to respiratory symptoms, affect lung function and reduce work ability. Thus, assessment of the influence of obesity on work ability, respiratory symptoms and lung function in adults with asthma is needed. Objectives: We hypothesized that patients with obesity and asthma have more respiratory symptoms and reduced work ability and lung function compared with normal-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…While it is well known that obesity and high BMI are associated with poor health outcomes for patients with chronic diseases [2,[41][42][43][44] including sarcoidosis, [45][46][47] their role in the etiology of these chronic diseases has only recently begun to be explored. [29,43,[48][49][50][51][52][53] Studies in the past two decades have shown that obesity is associated with an increased incidence of autoimmune diseases, and have expounded on the biological plausibility of that association.…”
Section: Discussionmentioning
confidence: 99%
“…While it is well known that obesity and high BMI are associated with poor health outcomes for patients with chronic diseases [2,[41][42][43][44] including sarcoidosis, [45][46][47] their role in the etiology of these chronic diseases has only recently begun to be explored. [29,43,[48][49][50][51][52][53] Studies in the past two decades have shown that obesity is associated with an increased incidence of autoimmune diseases, and have expounded on the biological plausibility of that association.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have suggested an inverse relationship between obesity and changes in lung function [ 13 , 16 ]. However, it is essential to note that most studies have only compared lung function in overweight or obese people with average weight [ 14 , 16 , 20 ], ignoring the possible effects of low body fat on lung function. Of course, we know that obesity is a severe problem in the world today.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation could be that airway narrowing and closure caused by obesity impede delivery of inhaled medications to the small airways [5]. Asthma patients with BMI >30 kg/m 2 have a higher symptom score which was reflected in reduced spirometry results but did not lead to reduced work ability as Klepaker et al [75] showed.…”
Section: Obese Phenotype In Asthmamentioning
confidence: 99%